Linkages between SMEs and Large Firms: Findings from a Survey in the Philippines - Jamil Paolo Fransisco; Tristan Canare (International Journal of Small and Medium Enterprises and Business Sustainability, 2018)
A recent strand of literature identifies linkages with large businesses as possible contributors to small and medium enterprises (SMEs) development. However, there is a dearth of empirical studies on this topic, particularly using data taken from the point of view of SMEs. Addressing this is the primary research problem of this paper. Using a survey of 530 SMEs and a series of key informant interviews in Metro Manila, Philippines, it specifically aims to study the benefits and costs to SMEs of linkages with large businesses, determine the extent of these linkages, analyze how they can contribute to SME development, and study if these linkages are associated to some SME success factors. Results suggest that 1) Philippine SMEs are not extensively linked to large firms, 2) the primary benefits to SMEs of linking with big firms are knowledge transfer and access to markets and the primary disadvantages are bureaucracy in large firms and their strong bargaining power, 3) these linkages generally have net positive benefits to SMEs from the SMEs’ point of view, and 4) some forms of linkages are associated with certain factors important to SME development. This paper also analyzed the obstacles faced by SMEs in linking with large firms and offered some policy solutions to address these.